Accelerating green innovation : essays on alternative investments in clean technologies - Migendt, Michael (Springer Gabler, 2017)
Michael Migendt explains the role of alternative investments in supporting the growth of a sustainable economy and recognizes levers that policy makers, managers and entrepreneurs could use for further accelerating green innovation through finance. He focuses on specific examples of alternative investments into green industries, companies, projects, and infrastructure, covering the developments along the innovation chain. Especially the acceleration of green technologies and the in this context occurring interrelations between the three areas of finance, innovation, and policy are key to this work. Contents *Emergence of Cleantech as an Investment Category - Media Attention and Venture Capital Investment *Private Equity in Clean Technology - An Exploratory Study of the Finance-Innovation-Policy Nexus *Public Policy Influence on Renewable Energy Investments - A Panel Data Study Across OECD Countries *Development of Industries in the Cleantech Sector - A Case of the Solar and Fuel Cell Industries Target Groups *Researchers and students in the fields of entrepreneurship, technology & innovation management, and energy economics *Policy makers, institutional investors, managers of private equity and venture capital funds The Author Dr. Michael Migendt wrote his dissertation under the supervision of Prof. Dr. Ronald Gleich at the Strascheg Institute for Innovation and Entrepreneurship (SIIE) at EBS Business School, EBS Universität für Wirtschaft und Recht in Wiesbaden.
Keywords: Business.; Entrepreneurship.; Management.; Industrial management.; Investment banking.; Securities.; Renewable energy sources.; elektronické knihy; electronic books